Kebutuhan Material Jaringan Jalan Provinsi di Provinsi Lampung tahun anggaran 2016 wilayah 1 dan 3 - Prawaka, Muhammad Hendro; Hadi, Yohanes Martono; Zakaria, Ahmad (Universitas Lampung, 2017)
This study was conducted to asses the material requiermens for provincial network in Lampung in budget year 2016 to obtain the results for the following year.From the calculation of material needs of Lampung province road workfor region 1 and 3 in 2016, it shows a considerable need for asphalt, cement, sands, stone. From the calculation analysis of government tendency to apply tender pattern is quite late. And giving impact on the latency of material supply needs of road works in Lampung Province.However, to meet the material needs of Lampung Province road works is quite good. Considering its fulfilled the smooth supply needs to meet the material recuirements.Keywords : material recruitmen, road networks, Lampung province